A model of gameful design for learning using interactive tabletops: enactment and evaluation in the socio-emotional education classroom - Ioannou, Andri (My University, 2019)
Building on established pedagogy and technological advancement, this article presents a model of gameful design for learning using interactive tabletops, enacted and evaluated in the context of socio-emotional education. Based on the proposed model, we detail the design of a technology-enhanced learning experience in which a series of traditional lessons are enriched by collaborative work on interactive tabletops; four gameful activities are used which may be directly linked to a school curriculum. We conduct a qualitative case study with the participation of 86 fifth grade students across two elementary schools which have a significant minority enrolment. We demonstrate the ways in which the students draw on recently-acquired knowledge, engage in dramatic play, share the digital space and collaborate intensively to achieve a new and refined understanding of concepts and behaviours linked to perspective-taking. We discuss how tabletops, in synergy with constructivist pedagogy and principles of gameful design, allow researchers and practitioners to promote communication, collaboration and perspective-taking in ways that were hitherto difficult to enact in traditional lessons. Gameful design for learning is seen as a multilevel endeavour, which involves the selection of tasks and tools as well as the behaviour of the learners and the instructor as participants in the learning environment.
Keywords: Collaboration; Interactive tabletops; Multicultural classroom; Peace education; Shareable surfaces; Social perspective taking; Technology-enhanced learning